The Origin and Molecular Epidemiology of Dengue Fever in Hainan Province, China, 2019 - Liu, Lin; Wu, Tao; Liu, Biao; Nelly, Rajaofera Mamy Jayne; Fu, Yumei; Kang, Xun; Chen, Chuizhe; Huang, Zenyan; Wu, Biao; Wang, Jiao; Zhu, Zhongyi; Ma, Jinmin; et al. (Frontiers in Microbiology, 2021)
There was an outbreak of Dengue fever on September 5, 2019, in Hainan Province, which has not been endemic for 28 years. We aim to describe the clinical and epidemiological features of the 2019 outbreak in Hainan Province and identify the cause. All type 1 Dengue fever cases that occurred in this outbreak of Hainan exhibited mild clinical symptoms. The epidemiological investigations indicate that the outbreak might originate from workers in the Xiuying area, Haikou City, form a concentrated outbreak, and then spread out. Bayesian phylogenies results and epidemiological data were used to infer a likely series of events for the dengue virus's potential spread and trace the possible sources. The strains' sequences were close to a sequence from the nearby Guangdong province, supporting the hypothesis that the dengue virus was imported from Guangdong province and then spread across Hainan province. Furthermore, it is interesting that two other strains didn't group with this cluster, suggesting that additional introduction pathways might exist. The study indicated that the dengue fever epidemic presented two important modes in Hainan. Firstly, epidemics prevalence was caused by imported cases, and then endogenous epidemics broke out in the natural epidemic focus.